2012
DOI: 10.1128/aac.05908-11
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of the Activities of the Novel Anticytomegalovirus Compound AIC246 (Letermovir) against Herpesviruses and Other Human Pathogenic Viruses

Abstract: AIC246 (letermovir) is a potent anticytomegalovirus drug in clinical development. Here, we report a consistent antiviral efficacy of AIC246 against human cytomegalovirus laboratory strains, clinical isolates, and virus variants resistant to approved drugs. Furthermore, we describe a remarkable selectivity of AIC246 for human cytomegaloviruses compared to that of other alpha-, beta-, or gammaherpesviruses or nonrelated pathogenic viruses, including adeno-, hepadna-, retro-, orthomyxo-, and flaviviruses. Our dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 20 publications
(13 reference statements)
0
53
0
3
Order By: Relevance
“…In fact, its novel mode of action not only appears to avoid the toxicities seen with the nucleoside analogues (19,20), but also offers new treatment options for patients infected with HCMV strains resistant to approved antivirals. The latter drug property is strongly supported by in vitro data, as well as initial clinical data relating to letermovir use in a lung transplant patient infected with a multiresistant HCMV strain (18,(22)(23)(24).…”
mentioning
confidence: 57%
“…In fact, its novel mode of action not only appears to avoid the toxicities seen with the nucleoside analogues (19,20), but also offers new treatment options for patients infected with HCMV strains resistant to approved antivirals. The latter drug property is strongly supported by in vitro data, as well as initial clinical data relating to letermovir use in a lung transplant patient infected with a multiresistant HCMV strain (18,(22)(23)(24).…”
mentioning
confidence: 57%
“…In line with its distinct mode of action, in vitro studies have shown that letermovir is active against HCMV strains resistant to current anti-HCMV drugs (4,5,7). In vivo confirmation of resistance-breaking potential was demonstrated in a patient infected with a multidrug-resistant HCMV strain (8).…”
mentioning
confidence: 87%
“…The clinical impact of drug-resistant CMV is enormous, as it has led to high rates of tissue-invasive disease, poor allograft survival, and heightened patient mortality (201,212). Treatment is very limited, and depending on the genetic profile, one may use highly nephrotoxic drugs, such as foscarnet and cidofovir (for UL97-exclusive mutants), or off-label and investigational drugs, such as leflunomide, maribavir, letermovir, and CMX-001 (201,(213)(214)(215).…”
Section: Relapse and Resistancementioning
confidence: 99%